THE MEANING OF PROFIT FROM THE PERSPECTIVE OF FRESH FISH TRADERS IN THE TRADITIONAL INPRES MARKET - Siti Atikah Rahayu; Fadhilla Septiani; Ade Ainun Ariyanti; Ernawaty Usman; Jamaluddin (RADJA PUBLIKA, 2025)
Background In the context of traditional traders, profit is understood not only as the difference between revenue and costs, but also has social, psychological, and spiritual significance inherent in their daily lives. Fresh fish traders in traditional markets view profit not simply as a measure of financial gain, but as a symbol of gratitude, a form of self-defense, and a foundation for family well-being. This phenomenon demonstrates that the concept of profit in the informal sector differs from the conventional, numbers-oriented accounting perspective. Objective This study aims to reveal the meaning of profit from the perspective of fresh fish traders at the Inpres Traditional Market through a phenomenological approach, as well as to explain how profit is understood in the economic and social life of traders. Research methods This research employed qualitative methods with a transcendental phenomenological approach. Data were obtained through in-depth interviews and observations of trading activities. Analysis was conducted by reducing traders' subjective experiences to key themes that fully illustrate the meaning of profit. Research result The research results show that profit is interpreted in five main forms: self-love (a form of self-respect), self-defense (defense against life's pressures), emergency savings (a strategy for dealing with unexpected situations), a foundation for family needs (a source of household economic needs), and spiritual steadfastness (a sense of gratitude for the sustenance received). The meaning of profit is not only economic but also emotional and spiritual. Originality/Novelty of Research This research provides a new perspective: profit for fresh fish traders is not simply an indicator of economic performance but also a reflection of the social, cultural, and spiritual values ​​that shape the identity of traders in traditional markets. These findings enrich contextual accounting studies that focus on human values.